Post-hoc reweighting of hadron production in the Lund string model - Assi, Benoît; Bierlich, Christan; Ilten, Philip; Menzo, Tony; Mrenna, Stephen; Szewc, Manuel; Wilkinson, Michael K.; Youssef, Ahmed; Zupan, Jure (SciPost Physics, 2025)
We present a method for reweighting flavor selection in the Lund string fragmentation model. This is the process of calculating and applying event weights enabling fast and exact variation of hadronization parameters on pre-generated event samples. The procedure is post hoc, requiring only a small amount of additional information stored per event, and allowing for efficient estimation of hadronization uncertainties without re-peated simulation. Weight expressions are derived from the hadronization algorithm itself, and validated against direct simulation for a wide range of observables and parameter shifts. The hadronization algorithm can be viewed as a hierarchical Markov process with stochastic rejections, a structure common to many complex simulations outside of high-energy physics. This perspective makes the method modular, extensible, and potentially transferable to other domains. We demonstrate the approach in PYTHIA 8, including both coverage considerations and timing benefits. For the purpose of this pa-per, our goal is to develop and demonstrate the the formalism, and we therefore exclude several model variations for baryon production (popcorn model, junction production) needed for proton collisions. These will be the topic of a future paper.
Publisher Copyright: © 2025, SciPost Foundation. All rights reserved.